Disclosure of domestic violence in mental health settings: A qualitative meta-synthesis. (August 2014) - Trevillion, Kylee; Hughes, Bryony; Feder, Gene; Borschmann, Rohan; Oram, Siân; Howard, Louise M.
Abstract Little is known about how psychiatric services respond to service users' experiences of domestic violence. This qualitative meta-synthesis examined the healthcare experiences and expectations of mental health service users experiencing domestic violence. Twenty-two biomedical, social science, grey literature databases and websites were searched, supplemented by citation tracking and expert recommendations. Qualitative studies which included mental health service users (aged ≥ 16 years) with experiences of domestic violence were eligible for inclusion. Two reviewers independently extracted data from included papers and assessed quality. Findings from primary studies were combined using meta-synthesis techniques. Twelve studies provided data on 140 female and four male mental health service users. Themes were generally consistent across studies. Overarching theoretical constructs included the role of professionals in identifying domestic violence and facilitating disclosures, implementing personalized care and referring appropriately. Mental health services often failed to identify and facilitate disclosures of domestic violence, and to develop responses that prioritized service users' safety. Mental health services were reported to give little consideration to the role of domestic violence in precipitating or exacerbating mental illness and the dominance of the biomedical model and stigma of mental illness were found to inhibit effective responses. Mental health services often fail to adequately address the violence experienced by mental health service users. This meta-synthesis highlights the need for mental health services to establish appropriate strategies and responses to domestic violence to ensure optimal care of this vulnerable population.